Meningkatkan harga diri anak slow learner melalui Child Centered Play Therapy - Iswinarti, Iswinarti; Hormansyah, Roselina Dwi (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractA slow learner is a child who has a delayed learning process. It affects other abilities such as adaptation, communication, and personality that can affect self-esteem. High self-esteem will make someone able to think positively about themselves and be more confident. One treatment to improve self-esteem is using Child-Centered Play Therapy (CCPT). It helps children to explore themselves through play media. This study aimed to see the effect of CCPT on the improvement of self-esteem in slow learner children. This study designed by using a quasi-experiment with a control group also pre-test and post-test. Subjects were 20 people with 9-11 years age range who were identified as slow learners. There were two groups in this study: experimental groups and the control groups that each contained 10 children. Rosenberg Self-Esteem (RSE) was used as an instrument of self-esteem (?=0,85). The data analysis method used Wilcoxon and Mann-Whitney tests. It proved that Child-Centered Play Therapy (CCPT) was effective in increasing the self-esteem of children who were slow learners. Slow learner children can increase their self-esteem through fun activities. Keyword: Child centered play therapy; Self-esteem; Slow learner AbstrakAnak dengan slow learner adalah seorang anak yang mengalami keterlambatan dalam proses belajar. Keterlambatan ini berpengaruh terhadap kemampuan lainnya seperti adaptasi, komunikasi dan pribadi yang dapat memberi dampak terhadap harga diri. Anak dengan harga diri yang tinggi membuat mereka dapat berpikir positif mengenai dirinya sendiri dan lebih percaya diri. Salah satu bentuk penanganan untuk meningkatkan harga diri adalah menggunakan Child Centered Play Therapy (CCPT). Terapi ini membantu anak mengeksplorasi diri melalui media bermain. Tujuan penelitian ini adalah untuk melihat pengaruh CCPT terhadap peningkatan harga diri anak slow learner. Desain penelitian menggunakan eksperimen quasi dengan kelompok kontrol serta pre-test dan post-test. Terdapat dua kelompok dalam penelitian, yaitu kelompok eksperimen yang terdiri atas 10 anak, dan kelompok kontrol juga terdiri atas 10 anak. Rosenberg Self Esteem (RSE) digunakan sebagai instrumen untuk mengukur harga diri (?=0,85). Teknik analisis data menggunakan uji Wilcoxon dan Mann Whitney. Hasil penelitian menunjukan bahwa Child Centered Play Therapy (CCPT) efektif meningkatkan harga diri anak slow learner. Anak slow learner dapat meningkat harga dirinya melalui terapi yang menyenangkan yaitu melalui bermain. Kata kunci: child centered play therapy; self-esteem; slow learner